A prática educativa de valores humanos universais através do ensino religioso com crianças e adolescentes do ensino fundamental - Sarquiz, Moisés Manir (2012)
The teaching of universal values in educational practice today represents a major challenge for the educational system in general. This exploratory study proposes to present the theme of universal human values in their theoretical nature and to expose how these values can be presented in Religious Education classes, through an inter-religious proposal for elementary school students from public and private schools. The first part discusses the nature of different universal values lived by humanity, in a classical way, by several authors, with emphasis on absolute and eternal values. The second part presents the concepts of different human values throughout history by various Greek philosophers as well as the main theologians of the Christian Church. Besides, it requests the thought of philosophers and educators of modernity. The theoretical exploration of many of these authors turns possible to offer a clear and distinct idea of the evolution and influence of universal values both of civil and spiritual order considered and experienced in the culture by humanity over millenniums. It also intends to design the future concerning to the tendency of education for the twenty-first century. The third part presents the application of universal human values in codes and laws, noticing the use and influence of the spirituality to human organization and social life. The forth part concludes the exploration presenting issues concerning pedagogical ideal practice for the application of teaching values to children and adolescents of elementary school and, with the object defined in order to be reach, considering some factors as content, approach and attitude of the teacher during the teaching-learning process. Then the study reports two experiences lived by the author concerning to the teaching of universal values for children and adolescents. The study ends presenting a survey with 5,160 students from high schools in the Greater São Paulo.